Temporal Assessment of the Effect of Flooding Vulnerability on Agricultural Land Use in the Gambia - Ibol, Philip Mopnang (Faculty of Geography, Universitas Gadjah Mada, 2023)
Flooding is a significant environmental problem, projected to intensify from 2010 to 2030. This natural disaster has affected several regions globally, leading to loss of life and property, community disruption, economic loss, injuries, and deaths. Factors contributing to flooding include heavy rainfall, rising sea levels, lowlands, waterways, climatic variations, wetlands, soil types, and unplanned urban settlements. The most severe case in the history of the Gambia struck in 2022. Therefore, this study aimed to identify areas vulnerable to flooding and the effect on agricultural land in the Gambia, as well as suggest preventive measures. The method adopted included the collection of secondary data from Landsat ETM imagery, Digital Elevation Model, rainfall data, Copernicus Global Land Services (CGLS), and Food Agricultural Organisation soil maps. The satellite imageries were processed and classified using ArcGIS 10.7.1, generating land use and land cover, slope, drainage density, rainfall, and soil maps. ArcGIS, combined with the Analytic Hierarchy Process (AHP), was used to integrate these maps to produce a vulnerability map for the study. The results showed areas with very high, high, moderate, low, and very low vulnerability. Based on the classification, coastal and lowland regions were in the high category. Therefore, this study recommended the construction of water barricades in vulnerable coastal areas to mitigate the disaster.